Improved performance evaluation of a dual passage solar thermal collector using staggered turbulators - Thakur, Abhishek; Kumar, Raj; Lee, Daeho; Kumar, Sushil; Kumar, Pawan; Asif, Mohammad; Agbulut, Umit (ELSEVIER, 2024)
Energy exists in various forms and plays a crucial role in global economic development and modernization. Solar energy is a prominent choice among several alternatives as an energy source to meet the demand. To harness solar energy for heating applications, the most basic approach is to transform it into thermal energy through the use of solar thermal collectors (STC). The thermal effectiveness of the dual passage solar thermal collector (DP-STC) is particularly poor. An effective approach to enhancing its thermohydraulic performance (eta(THPP)) involves employing turbulators on the absorber plate (AP). This study investigates the impact on eta(THPP) of DP-STC provided with single V-shaped staggered baffles (SVSSBs). The impact of various geometrical elements, such as relative staggered baffle position (P-B '/P-B) ranging from 0.45 to 0.75, relative staggered baffle size (B/HB) from 2.5 to 4.0, and relative roughness pitch (P-B/H-B) from 1.0 to 2.5, are investigated for Reynolds numbers (Re-X) ranging from 3000 to 19000. The remaining geometrical parameters, including the relative roughness height (H-B/H-C) = 0.40, relative gap position (G(d)/L-v) = 0.67, relative gap size (g/H-B) = 1, and angle of attack (alpha(B)) = 60 degrees, remained fixed. Notable among the findings of this research is the fact that, SVSSBs performed best in comparison to other turbulators reported in the literature review. The eta(THPP) reached its maximum value of 3.67 for the case with SVSSBs with P-B/H-B = 1.5, P-B '/P-B = 0.65, andB/HB = 3.5 atRe(X) = 17000. The correlations are also developed for the Nusselt number (Nu(BP)) and friction factor (f(BP)), using experimental data.
Keywords: Solar energy; Dual passage solar thermal collector; Single V-shaped staggered baffles; Geometrical parameters; Thermohydraulic performance; FRICTION FACTOR CORRELATIONS; AIR HEATER DUCT; BROKEN ARC RIB; ARTIFICIAL ROUGHNESS; RECTANGULAR DUCT; WIRE MESH; ENHANCEMENT; STORAGE; ENERGY; Thermodynamics; Energy & Fuels; Engineering; Mechanics